1996
DOI: 10.1042/bj3180459
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of a novel membrane-linked metalloproteinase from human myeloma cells

Abstract: We have isolated a novel cDNA from human myeloma cells encoding a member of the reprolysin family of metalloproteinases. Derived amino acid sequence predicts a protein of approx. 76 kDa. The open reading frame predicts the presence of a leader peptide, a pro-peptide with a 'cysteine switch', a metalloproteinase domain, a disintegrin-like domain, a cysteine-rich domain, an epidermal growth factor-like domain and a putative transmembrane sequence. Expression of the mRNA for this metalloproteinase has been demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…In addition, ADAM‐9 has been reported to be able to shed the ectodomain of membrane‐anchored heparin‐binding EGF‐like growth factor from Vero‐H cells (Izumi et al , 1998). Although it is unclear whether TACE or ADAM‐9 will process other membrane‐bound proteins, we have shown that myeloma cells express these, and other, members of the ADAM family (McKie et al , 1996 and unpublished observations). Syndecan‐1 shedding has been reported to be mediated by a TIMP‐3‐sensitive metalloproteinase in P3X63 cells, supporting a role for an ADAM‐like enzyme in this process (Fitzgerald et al , 2000).…”
Section: Discussionmentioning
confidence: 89%
“…In addition, ADAM‐9 has been reported to be able to shed the ectodomain of membrane‐anchored heparin‐binding EGF‐like growth factor from Vero‐H cells (Izumi et al , 1998). Although it is unclear whether TACE or ADAM‐9 will process other membrane‐bound proteins, we have shown that myeloma cells express these, and other, members of the ADAM family (McKie et al , 1996 and unpublished observations). Syndecan‐1 shedding has been reported to be mediated by a TIMP‐3‐sensitive metalloproteinase in P3X63 cells, supporting a role for an ADAM‐like enzyme in this process (Fitzgerald et al , 2000).…”
Section: Discussionmentioning
confidence: 89%
“…In this capacity, plasma cell MMP may play a crucial role in the connective tissue destruction in diseases such as RA and scleritis. Recently, McKie et al [32] cloned a novel 76-kDa membrane-associated MMP from human myeloma cells and suggested the potential involvement of this proteinase in the ECM degradation observed in multiple myeloma (a plasma cell neoplasm).…”
Section: Discussionmentioning
confidence: 98%
“…The mechanism by which the soluble form of syndecan‐1 is generated is not fully clear. Syndecan‐1 may be shed from the surface of cells by proteases such as MMP‐9 and ADAM12 (a disintegrin and metalloprotease 12) or by non‐matrix‐type metalloproteinases (19–21).…”
Section: Discussionmentioning
confidence: 99%